BANGGAI YAM DEVELOPMENT STRATEGY BASED INTERPRETATIVE STRUCTURAL MODELLING FOR FOOD SECURITY IN BANGGAI ISLANDS - Katili, Hidayat Arismunandar; Syartinilia, Syartinilia; Firmansyah, Irman; Widiatmaka, Widiatmaka (Faculty of Animal and Agricultural Science, Diponegoro University, 2025)
The agricultural sector significantly contributes to economic growth at local and national levels, reflecting broader social changes to improve materially and spiritual better living conditions. This research aims to assess income levels and identify constraints in the development of Banggai yam as a local food source. The research was conducted in the Banggai Islands Regency using quantitative descriptive analysis and the Interpretative Structural Modelling (ISM) approach. Respondents were selected using a stratified purposive sampling technique, resulting in 76 interviews, which included 68 farmers, 2 financial institutions, 4 government representatives, and 2 academics from the region. Findings show that Banggai yam farming generates significant financial returns, increasing farmers' income over the course of one growing season, thus categorizing it as a viable farming practice in the Banggai Islands Regency. Six key strategies for developing Banggai yam as a local food source were identified: government support (E7), farmer training and mentoring (E8), uncoordinated marketing (E1), annual Banggai yam cultivation (E5), shifting cultivation practices (E6), and unregulated land use (E14). Effectively addressing these constraints and prioritizing strategies will ultimately drive the goal of increasing incomes and guide the sustainable development of Banggai yam in the Banggai Islands Regency